2017
DOI: 10.1038/s41467-017-02116-9
|View full text |Cite|
|
Sign up to set email alerts
|

Stateful characterization of resistive switching TiO2 with electron beam induced currents

Abstract: Metal oxide resistive switches are increasingly important as possible artificial synapses in next-generation neuromorphic networks. Nevertheless, there is still no codified set of tools for studying properties of the devices. To this end, we demonstrate electron beam-induced current measurements as a powerful method to monitor the development of local resistive switching in TiO2-based devices. By comparing beam energy-dependent electron beam-induced currents with Monte Carlo simulations of the energy absorptio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 65 publications
1
21
0
Order By: Relevance
“…In more recent papers, Kumar et al reported modifications of the region surrounding the CFs generated in Pt/Hf/HfOx/Pt [24] and Pt/TiN/HfO2/Pt [25] devices as well. Similar effects were described in Hoskins et al for CFs in TiO2-based MIM devices with Pt electrodes [26]. Experimental results seem to indicate a permanent change of the oxide properties in the vicinity of the failure site which does not generate a deformation of the metal electrode [27].…”
Section: Effects Of Severe Electrical Stresssupporting
confidence: 84%
“…In more recent papers, Kumar et al reported modifications of the region surrounding the CFs generated in Pt/Hf/HfOx/Pt [24] and Pt/TiN/HfO2/Pt [25] devices as well. Similar effects were described in Hoskins et al for CFs in TiO2-based MIM devices with Pt electrodes [26]. Experimental results seem to indicate a permanent change of the oxide properties in the vicinity of the failure site which does not generate a deformation of the metal electrode [27].…”
Section: Effects Of Severe Electrical Stresssupporting
confidence: 84%
“…The migration of oxygen vacancies in the thicker TiO 2 layer and the charge trapping phenomenon at the heterointerfaces are the most plausible reasons for the distinguished resistive switching behavior of this specific sample. 31,32 The HRS currents of the Pt/TiO 2 -In 2 O 3 (N 2 )/ Au unit are in the region of 10 À4 ampere and the LRS ones are in the region of 10 milliampere (Fig. 4c).…”
Section: The Resistive Switching Mechanismmentioning
confidence: 97%
“…51 , American Chemical Society ( b ); ref. 52 , Nature Publishing Group ( c ); and ref. 53 , Nature Publishing Group ( d ); ref.…”
Section: Memristive Switching Studied By In Situ Techniquesmentioning
confidence: 99%
“…The local distribution of an electronic structure in TiO 2 -based memristors was measured with in situ electron beam-induced current (EBIC), as shown in Fig. 4c, providing a clear image of the underlying switching region, and reveals propagating polarization domains of symmetrical device structures 52 . Electron transport and electrochemical reactions of HfO 2 -based memristors were investigated with in situ CAFM.…”
Section: Memristive Switching Studied By In Situ Techniquesmentioning
confidence: 99%